2005
DOI: 10.1007/s11265-005-4841-x
|View full text |Cite
|
Sign up to set email alerts
|

Run-Time Reconfigurable Systems for Digital Signal Processing Applications: A Survey

Abstract: Today's digital signal processing (DSP) applications use computationally complex and/or adaptive algorithms and have stringent requirements in terms of speed, size, cost, power consumption, and throughput. Efficient hardware implementation techniques should be employed to meet the requirements of these applications. Run-Time Reconfiguration (RTR) is a promising technique for reducing the hardware required for implementing DSP systems as well as improving the performance, speed and power consumption of these sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 120 publications
0
17
0
Order By: Relevance
“…The tasks performed by the reconfigurable hardware are usually known as hardware tasks. By dynamically reconfiguring, these systems allow many hardware tasks to be mapped onto the same hardware platform, thus reducing the area and power consumption of the design [4]. In a dynamically reconfigurable system, the sequence of computation and configuration is just determined and handled at run-time.…”
Section: Evolution Of System-on-chipsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tasks performed by the reconfigurable hardware are usually known as hardware tasks. By dynamically reconfiguring, these systems allow many hardware tasks to be mapped onto the same hardware platform, thus reducing the area and power consumption of the design [4]. In a dynamically reconfigurable system, the sequence of computation and configuration is just determined and handled at run-time.…”
Section: Evolution Of System-on-chipsmentioning
confidence: 99%
“…dynamic reconfiguration) or compile-time (i.e. static reconfiguration) [4]. Static reconfiguration is the common way for implementing applications with FPGA (Fieldprogrammable Gate Arrays)-like reconfigurable logic fabric.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the previously reviewed work on DPR, there exist two other significant references discussing the advantages and challenges in DPR [117], [118].…”
Section: Dynamic Partial Reconfiguration (Dpr)mentioning
confidence: 99%
“…Shoa and Shirani [117] thoroughly explain different issues in run-time reconfiguration (RTR) systems, and list the implemented systems which support RTR reconfiguration as well as discussing different applications of, and the improvements achieved by applying RTR. An evaluation of DPR for signal and image processing is presented in [118].…”
Section: Dynamic Partial Reconfiguration (Dpr)mentioning
confidence: 99%
“…Because of the partial reconfiguration capability in an FPGA, studies have shown that an FPGA-based reconfigurable hardware system can improve performance for many applications [Hauck 1998;Tessier and Burleson 2001;Shoa and Shirani 2005]. For example, Chaubal [2004] successfully implemented a partially reconfigurable network controller onto a Xilinx Virtex XCV1000 FPGA device.…”
Section: Introductionmentioning
confidence: 99%